Extraction Of Nanocellulose From Sugarcane Bagasse Using Different Acids And Its Effects On Poly(Lactic Acid) - Gan, Ivy (Universiti Sains Malaysia, 2017)
The usage of abundant sugarcane bagasse as a source for the extraction of cellulose nanocrystals (CNC) would reduce waste in the environment. Strong acid hydrolysis by sulphuric acid (H2SO4) was a common method to produce CNC but the negative charged sulphate group on the surface of CNC had reduced the thermal properties and caused poor compatibility with poly(lactic acid) (PLA). This present study is to determine the feasibility of utilizing mild acid, phosphoric acid (H3PO4) to produce better thermal properties of CNCs and improved its compatibility with PLA. In this study, CNCs was extracted from sugarcane bagasse through alkaline treatment followed by acid hydrolysis. The obtained CNCs were then incorporated in PLA matrix to produce nanocomposite by solution casting method. The surface characteristics and thermal properties of different acid derived CNCs and the PLA/CNC nanocomposite were determined. The X-ray Photoelectron Spectroscopy (XPS) result showed that S-CNC (CNC by H2SO4 hydrolysis) was having slightly higher oxygen/carbon (O/C) ratio than P-CNC (CNC by H3PO4 hydrolysis). The particle size of P-CNC was smaller than S-CNC, however, the zeta potential of S-CNC is higher than P-CNC. The Fourier Transform Infra-Red Spectroscopy (FTIR) result indicated that PLA/P-CNC-10 gave better compatibility compared to PLA/S-CNC-10 nanocomposites. The degree of crystallinity (Xc) of PLA/P-CNC-10 is higher than the PLA/S-CNC-10. Thermogravimetric Analysis (TGA) results indicate that P-CNC could increase the thermal stability of PLA/P-CNC-10 nanocomposites.